(untitled) (Journal of Mathematical Modeling and Fractional Calculus, 2024)
In this paper, we investigate a fractional model for the COVID-19 epidemic that contains an antiretroviral treatment compartment. We implement novel methods to acquire effective results. We discuss equilibrium point, reproductive number, and sensitivity analysis. We utilize the Sumudu transform technique to obtain approximate solutions for the model, and we explore chaos control to assess stability around equilibrium points. We demonstrate the numerical simulations to prove the accuracy of the proposed techniques. The graphs illustrate how varying fractional orders impact the dynamics of each epidemiological group, revealing the memory and time-dependent effects on disease spread and control strategies.